Research of Arc Segment Metal Block Contact Character of Metal Belt Continuously Variable Transmission - Zhang Wu; Guo Wei; Zhang Wugang; Xing Le; Zhou Xuegang (Jixie chuandong)
Taking the contact characteristic of the arc segment metal block with metal belt type continuously variable transmission as study object,the mathematical model and finite element model are established.The results show that the numerical solution of the stress and deformation is basically the same as that of the analytical solution,but the numerical value is higher,the reason is that the contact area of the metal block is reduced. With the increase of the thickness of the metal block,the compressive stress decreases gradually in the z direction,but the rate is very fast,it meets to Saint Venant principle. This study lays a theoretical foundation for the optimization of metal block structure and so on.